A proposal for the elimination of export restrictions on food products - Bianchi, Eduardo; Piñeiro, Martín (2017)
The episodes of higher and volatile food prices during 2007-2008 and 2011-2012 have raised concerns about the role of agricultural export restrictions in further raising international prices and its impact on the food- insecure population in net food-importing developing countries. Although many arguments have been invoked to justify the application of export restrictions, mainly food security concerns, it is clear not only from theoretical studies but also from historical research, that these measures have a multiplier effect on spikes and the volatility of international prices. The negative impacts of these beggar-thy-neighbor policies are widespread among countries, although they have been more severe in those less developed net food- importing countries, with a large share of their population being the urban poor. Moreover, significant damage to trust in the world market as a reliable source of food was inflicted during these food crises.